Analisis Kesesuaian Habitat Peneluran Penyu Sisik (Eretmocheyls imbricata) di Pantai Batu Hitam dan Pantai Bama, Taman Nasional Baluran, Situbondo - Yusril Zaqi Ubaydillah; Defri Yona; Rarasrum Dyah Kasitowati (Jurnal Kelautan Tropis, 2023)
Hawksbill turtles were observed nesting along the coast of Baluran, mainly at Batu Hitam Beach. The eggs were relocated to a hatchery on Bama Beach, which is a beach where hawksbill turtles have never been seen laying eggs naturally. Referring to the natal homing/philopatry hypothesis, hatchlings that are released on Bama Beach will likely come back to lay eggs in the future. Meanwhile, Batu Hitam Beach is planned to be developed into a tourist area. To preserve this important nesting area, a nesting habitat suitability assessment is needed that can contribute to effective conservation planning and management. This study used observational data to identify the bio-physical characteristics of the beaches and analyzed them using the habitat suitability index (HSI). The parameters observed were the width and slope of the beach, percentage of sand, intensity of light, coastal vegetation, percentage of buildings, and the distance between the nesting beach and the feeding area. There were no significant differences in bio-physical characteristics between the two beaches. Except for beach width, all other parameters are given the same score. Batu Hitam Beach has a slightly wider and steeper beach than Batu Hitam Beach.  Based on the results of an assessment utilizing the habitat suitability index (HSI) for hawksbill nesting sites, the biophysical conditions of Bama Beach and Batu Hitam Beach were assessed as very suitable (>68.86%). Despite Bama Beach's suitability, there have been no reports of hawksbill turtles nesting there. The width of the beach that is too narrow and a lack of coastal vegetation shade are thought to have forced the hawksbill to prefer other locations, such as Batu Hitam Beach.  Penyu sisik teramati bertelur di sepanjang pesisir Baluran, terutama di Pantai Batu Hitam. Telur yang ditemukan dipindahkan ke tempat penetasan di Pantai Bama, pantai yang belum pernah tercatat penyu bertelur secara alami. Merujuk pada hipotesis natal homing/philopatry, tukik yang dilepasliarkan di Pantai Bama dimungkinan akan kembali untuk bertelur di kemudian hari. Di sisi lain, Pantai Batu Hitam rencananya akan dikembangkan menjadi kawasan wisata. Untuk melestarikan habitat peneluran ini, diperlukan penilaian kesesuaian habitat bersarang yang dapat berkontribusi pada perencanaan dan pengelolaan konservasi yang efektif. Penelitian ini menggunakan pendekatan observasional untuk mengidentifikasi karakteristik bio-fisik pantai dan menganalisisnya menggunakan indeks kesesuaian habitat (IKH). Parameter yang diamati adalah lebar dan kemiringan pantai, persentase pasir, intensitas cahaya, vegetasi pantai, persentase bangunan, dan jarak antara pantai peneluran dengan area pakan. Tidak terdapat perbedaan kondisi bio-fisik yang signifikan antara kedua pantai tersebut. Seluruh parameter mendapatkan skor yang sama, kecuali lebar pantai. Pantai Batu Hitam memiliki pantai yang sedikit lebih lebar dan lebih curam daripada Pantai Batu Hitam. Berdasarkan hasil penilaian dengan memanfaatkan Indeks Kesesuaian Habitat (IKH) peneluran penyu sisik, kondisi bio-fisik Pantai Bama dan Pantai Batu Hitam dinilai sangat sesuai (>68,86%). Meskipun hasil penilaian kondisi Pantai Bama sesuai menjadi habitat peneluran, belum ada laporan penyu sisik bertelur di sana. Lebar pantai yang terlalu sempit dan kurang meratanya naungan vegetasi pantai diduga menjadi penyebab penyu sisik memilih pantai lain di sekitar Pantai Bama, salah satunya adalah Pantai Batu Hitam.